A Legal and Institutional Framework for Sustainable Management of Forest Resources in Southern Sudan : Policy note - World Bank (World Bank, 2012)
This policy note was prepared in response to a request from the Government of Southern Sudan (GoSS) for World Bank assistance in developing legislative and institutional policies and strategies that will take advantage of the potential of the region's forest resources to contribute to poverty alleviation, food security, sustainable agriculture, economic growth, and to protection of forest-related environmental services such as climate, biodiversity, water, and wildlife resources. The note is intended to: (a) take stock of the current situation on the ground, including identifying the legislative, institutional, governance, and policy reforms needed to create an enabling environment for both public and private-sector investment. This should help in contributing to improved understanding of the currently underutilized potential of Southern Sudan's forest resources; (b) analyze what has worked and what has not worked prior to and since the signing of the Comprehensive Peace Agreement (CPA); and (c) suggest priority solutions and actions towards revitalizing the forestry sector. Key policy issues addressed in this note include: 1) strengthening forest resource information and knowledge base; 2) developing a coherent legislative and policy framework, organizational structure, and capacity for the sector; 3) promoting participatory forest and woodland management; 4) enabling forest-based industries to thrive; 5) creating an enabling environment for attracting private-sector investment; 6) protecting and enhancing forest-related environmental services; 7) using technical approaches to conservation and sustainable management of forest resources; and 8) introducing predictable and sustainable long-term financing mechanisms.